Remaillage en grandes déformations: Applications à la mise en forme de structures 2D - Borouchaki, Houman; Cherouat, Abdelhakim; Saanouni, Khemais; Laug, Patrick (European Journal of Computational Mechanics, 2002)
The analysis of the mechanical structures using Finite Element Method in the framework of large elastoplastic strain, needs frequent remeshing of the deformed domain during the computation. Indeed, the remeshing is due to the large geometrical distortion of finite elements or the adaptation to the physical behavior of the solution. This paper gives the necessary steps to remesh the mechanical structure during the large elastoplastic deformation with damage. These steps are essentially constituted by geometrical and physical error estimates. The proposed method is integrated in the ABAQUS computational code and some numerical examples show the efficiency of our method in the case of finite transformations with damage.